2017
DOI: 10.2967/jnumed.117.193201
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor DNA Reflects Tumor Metabolism Rather Than Tumor Burden in Chemotherapy-Naive Patients with Advanced Non–Small Cell Lung Cancer: 18F-FDG PET/CT Study

Abstract: We aimed to evaluate the relationships between circulating tumor cells (CTCs) or plasma cell-free DNA (cfDNA) on one side and a comprehensive range of F-FDG PET/CT-derived parameters on the other side in chemotherapy-naive patients with advanced non-small cell lung cancer (NSCLC). From a group of 79 patients included in a trial evaluating the role of pretreatment circulating tumor markers as predictors of prognosis in chemotherapy-naive patients with advanced NSCLC, we recruited all those who underwent F-FDG P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 19 publications
3
32
1
Order By: Relevance
“…For example, when considering intratumor heterogeneity, subclones carrying driver mutations are more prone to release DNA [20]. However, some researches [21] in non-small cell lung cancer (NSCLC) have indicated that the cfDNA level is correlated with tumor metabolism and reflects tumor biological behaviors rather than tumor burden, potentially because nontumor DNA is also increased during tumor progression due to interactions between tumor cells and adjacent healthy tissue cells [22].…”
Section: Origin Of Ctdnamentioning
confidence: 99%
See 2 more Smart Citations
“…For example, when considering intratumor heterogeneity, subclones carrying driver mutations are more prone to release DNA [20]. However, some researches [21] in non-small cell lung cancer (NSCLC) have indicated that the cfDNA level is correlated with tumor metabolism and reflects tumor biological behaviors rather than tumor burden, potentially because nontumor DNA is also increased during tumor progression due to interactions between tumor cells and adjacent healthy tissue cells [22].…”
Section: Origin Of Ctdnamentioning
confidence: 99%
“…In addition to the tumor volume [125,133,134], it is also associated with factors such as necrosis, ki67, pathological type, lymph node metastasis, hematogenous metastasis, allele frequency, EpCAM-positive CTC mutation [135] and others [136]. The condition of ctDNA not only reflects the tumor burden but also relates to tumor metabolism, which indicates the biological behavior of the tumor [21].…”
Section: Ctdna and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Therefore, although the variability in ctDNA is typically attributed to the tumor burden, 46 it actually might reflect tumor metabolism. 47,48 For example, in patients with melanoma, ctDNA levels were correlated with metabolic disease volume, estimated with 18 F-labelled fluorodeoxyglucose positron emission tomography. 49,50 Therefore, the ctDNA level was a complex reflection of tumor biology, rather than simply associated with tumor burden or the number of dying cells.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline wholebody metabolically active tumor volume (WB-MATV), representing the patient's active tumor load before treatment, was recently validated by our group as a strong prognostic imaging biomarker in a large cohort of chemorefractory mCRC patients (16). Interestingly, another PET parameter evaluating the glycolytic activity of the disease, SUV max , was recently reported to be correlated with cfDNA in advanced non-small cell lung cancer patients (17).…”
mentioning
confidence: 99%